2016
DOI: 10.2147/copd.s118692
|View full text |Cite
|
Sign up to set email alerts
|

Endocan and the respiratory system: a review

Abstract: Endocan, formerly called endothelial cell-specific molecule 1, is an endothelial cell-associated proteoglycan that is preferentially expressed by renal and pulmonary endothelium. It is upregulated by proangiogenic molecules as well as by pro-inflammatory cytokines, and since it reflects endothelial activation and dysfunction, it is regarded as a novel tissue and blood-based relevant biomarker. As such, it is increasingly being researched and evaluated in a wide spectrum of healthy and disease pathophysiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 84 publications
1
38
0
3
Order By: Relevance
“…ESM1 protein, also known as endocan, is a dermatan sulfate proteoglycan which is primarily expressed in ECs of vascular tissues including capillaries and arterioles but can also be found in the ECs of other tissues such as human lung and kidney . Its gene expression is regulated by cytokines, indicating its possible implication in endothelium‐based disorders . In addition, in recent studies, ESM1 has been identified as a specific biomarker of tip cells during angiogenesis as well as a simultaneous target and modulator of VEGF signaling in ECs .…”
Section: Discussionmentioning
confidence: 99%
“…ESM1 protein, also known as endocan, is a dermatan sulfate proteoglycan which is primarily expressed in ECs of vascular tissues including capillaries and arterioles but can also be found in the ECs of other tissues such as human lung and kidney . Its gene expression is regulated by cytokines, indicating its possible implication in endothelium‐based disorders . In addition, in recent studies, ESM1 has been identified as a specific biomarker of tip cells during angiogenesis as well as a simultaneous target and modulator of VEGF signaling in ECs .…”
Section: Discussionmentioning
confidence: 99%
“…It is secreted by vascular endothelial cells, and also expression of endocan is regulated by a number of proangiogenic factors such as vascular endothelial growth factor as well as cytokines. 9 11 , 36 Previous studies mentioned that endocan not only plays a role in the inflammatory process but also plays a role in the vascular damage and endothelium-dependent pathological disorders. Therefore, it may represent a novel endothelial cell dysfunction marker.…”
Section: Discussionmentioning
confidence: 99%
“…It is preferentially expressed in vascular endothelial cells in the lung and kidney, and its overexpression can be seen in some neonatal and proliferating tissues as well as some tumors. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%